Role of Proximal Optimization Technique Guided by Intravascular Ultrasound on Stent Expansion, Stent Symmetry Index, and Side-Branch Hemodynamics in Patients With Coronary Bifurcation Lesions. (October 2017) - Hakim, Diaa; Chatterjee, Arka; Alli, Olusuen; Turner, Joshua; Sattar, Assad; Foin, Nicolas; Leesar, Massoud A.
Abstract : Background—: Bench models of coronary bifurcation lesions demonstrated that the proximal optimization technique (POT) expanded the stent and opened the side branch (SB). We investigated the role of POT guided by intravascular ultrasound on the main vessel (MV) stent expansion and SB fractional flow reserve (FFR) in patients with coronary bifurcation lesion. Methods and Results—: In 40 patients with coronary bifurcation lesion, 120 intravascular ultrasound examinations of the MV were performed at baseline, after MV stenting, and POT followed by 95 FFR measurements of the SB. In the proximal stent segment, stent volume index and minimum stent area were larger after POT versus MV stenting (9.2±3.4 versus 7.40±2.0 mm 3 /mm and 7.65±1.8 versus 6.38±1.7 mm 2, respectively; P <0.01). In the bifurcation segment, minimum stent area was larger after POT versus MV stenting (6.45±2.1 versus 5.9±2.0 mm 2, respectively; P <0.05). POT expanded the stent symmetrically. After POT, SB FFR was <0.75 in 12 patients (30%), which improved to >0.75 after SB dilation or SB stenting+final POT. SB FFR was significantly higher after POT+SB dilation or SB stenting+final POT versus after MV stenting and POT. Conclusions—: This is the first study of POT guided by intravascular ultrasound in patients with coronary bifurcation lesion, demonstrating that POT symmetrically expanded the proximal and bifurcation segments of the stent. After POT, SB FFR was <0.75 in a third of patients, which improved to >0.75 after SB dilation or SB stenting+final POT.